Answer:
-(20+z)/y = x
Step-by-step explanation:
-20=xy +z
Subtract z from each side
-20 -z = xy+z-z
-20 -z = xy
Divide each side by y
(-20 -z)/y = xy/y
Factor out a negative
-(20+z)/y = x
Answer:
I think the answer is.. .
Step-by-step explanation:
(b)
Answer:
The sum of two numbers is 14 and their difference is 10
Step-by-step explanation:
"2 numbers (x and y)
x+y = 14
and x-y + 10
If you each equation by positive 2, one gets 2x+2y = 28 and 2x-2y = 20
The 'y-terms' cancel out or equal zero when adding, so 4x = 48, divide by 4 on each side and x or the first number equals 12.
Plug 12 back into the equation for 'x' and subtract 12 on both sides so that y=2
The difference of 12-2=10 and the addition of 12 and 2 equals 14"
hopes this helps
<u>Answer:</u>
The correct answer option is quadratic, because the height increases and then decreases.
<u>Step-by-step explanation:</u>
We are given the following data in the table which represents the height of an object over time:
Time (s) Height (ft)
0 5
1 50
2 70
3 48
We know that in situation where the values increase and then decreases, a quadratic model is used.
From the values given in the table, we can see that the values of height first increased and then decreased with the increase in time.
Therefore, the model used is quadratic, because the height increases and then decreases.